The lower hippocampus global connectivity, the higher its local metabolism in Alzheimer disease - Tahmasian, Masoud; Pasquini, Lorenzo; Scherr, Martin; Meng, Chun; Foerster, Stefan; Bratec, Satja Mulej; Shi, Kuangyu; Yakushev, Igor; Schwaiger, Markus; Grimmer, Timo; Diehl-Schmid, Janine; Riedl, Valentin; et al. (Neurology, 2015)
Objectives: Based on the hippocampus disconnection hypothesis in Alzheimer disease (AD), which postulates that uncoupling from cortical inputs contributes to disinhibition-like changes in hippocampus activity, we suggested that in patients with AD, the more the intrinsic functional connectivity between hippocampus and precuneus is decreased, the higher hippocampal glucose metabolism will be. Methods: Forty patients with mild AD dementia, 21 patients with mild cognitive impairment, and 26 healthy controls underwent simultaneous PET/MRI measurements on an integrated PET/MR scanner. 18 F-fluorodeoxyglucose-PET was used to measure local glucose metabolism as proxy for neural activity, and resting-state functional MRI with seed-based functional connectivity analysis was performed to measure intrinsic functional connectivity as proxy for neural coupling. Group comparisons and correlation analysis were corrected for effects of regional atrophy, partial volume effect, age, and sex. Results: In both patient groups, intrinsic connectivity between hippocampus and precuneus was significantly reduced. Moreover, in both patient groups, glucose metabolism was reduced in the precuneus (AD < mild cognitive impairment < controls) while unchanged in the hippocampus. Critically, the lower connectivity between hippocampus and precuneus was in patients with AD dementia, the higher was hippocampus metabolism. Conclusion: Results provide evidence that in patients with AD dementia, stronger decrease of intrinsic connectivity between hippocampus and precuneus is linked with higher intrahippocampal metabolism (probably reflecting higher neuronal activity). These data support the hippocampus disconnection hypothesis, i.e., uncoupling from cortical inputs may contribute to disinhibition-like changes of hippocampal activity with potentially adverse consequences on both intrahippocampal physiology and clinical outcome.
CRIS-Team Scopus Importer:2022-11-28